2014
DOI: 10.1080/10640266.2014.964623
|View full text |Cite
|
Sign up to set email alerts
|

The Role of the Therapeutic Alliance in Eating Disorder Treatment Outcomes: A Systematic Review

Abstract: The therapeutic alliance has proven to be an important construct in psychotherapy outcomes research for numerous psychiatric disorders. Given that dropout rates from treatment are especially high for individuals with eating disorders, it is critical to clarify the role that the therapeutic alliance plays in predicting treatment outcomes for this specific population. MEDLINE, CINAHL, and PsycINFO databases were systematically reviewed for studies that formally measured the therapeutic alliance construct and at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
62
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(71 citation statements)
references
References 50 publications
(77 reference statements)
2
62
0
2
Order By: Relevance
“…therapeutic alliance, group cohesion or experience of universality among group members facilitating treatment effects. For EDs the impact of such mechanisms in CBT treatment is less understood [18, 3133, 35, 36] in particular with respect to BN and BED [34], and for obvious reasons completely unknown with respect to the novel physical exercise and dietary treatment program. The exploring of the impact of such mechanisms imply a search for the mediation effects and when such effects occur during the course of treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…therapeutic alliance, group cohesion or experience of universality among group members facilitating treatment effects. For EDs the impact of such mechanisms in CBT treatment is less understood [18, 3133, 35, 36] in particular with respect to BN and BED [34], and for obvious reasons completely unknown with respect to the novel physical exercise and dietary treatment program. The exploring of the impact of such mechanisms imply a search for the mediation effects and when such effects occur during the course of treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Recent literature reviews have shown inconsistent findings across ED diagnoses, treatments, patient age groups and time ( eg . early, mid or late) of assessment [31, 35, 36]. We hence included measures of alliance and group climate after every CBT and PED-t session to study the temporal order between these factors and response in both treatment arms [31].…”
Section: Introductionmentioning
confidence: 99%
“…In our case, CRT sessions were dedicated exclusively to the specific needs and circumstances of each individual, and it is not unlikely that such exclusivity could have had a positive effect in strengthening the therapist–patient bond. A good therapeutic alliance is known to predict treatment adherence and better outcomes in patients with EDs [46], especially young patients [47], and previous research in eating disorders suggests that treatment satisfaction is closely related to the way in which care is delivered [48]. In the current study, the vast majority of patients chose the most favorable response outcome (“very good”) when asked about the collaboration between the patient and the therapist, and the remaining therapist-specific items were answered equally, positively affirmative.…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review [30] of the role of alliance in eating disorder treatment outcome in adults and adolescents highlights the lack of conformity in alliance measures used, differences in definition of what is early, mid and late alliance and the consequent difficulty in drawing general conclusions from the few studies that exist. Although the data from the existing studies are still fairly limited, the studies of the role of therapeutic alliance in adolescent anorexia nervosa seem consistent with findings outside of the eating disorder field showing that adolescent and parent ratings of alliance are not interchangeable and tend to relate to different aspects of treatment outcome.…”
Section: Therapeutic Alliancementioning
confidence: 98%